2021
DOI: 10.1007/s12079-021-00607-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of nuclear factor kappa B (NF-κB) in filarial pathology

Abstract: The transcription factor NF-κB promotes immunity by controlling the expression of genes involved in inflammation. Cytokines and pathogen-associated molecular patterns stimulate cell surface receptors, including toll-like receptors, to initiate a signalling cascade resulting in the activation of NF-κB. NF-κB drives the expression of target genes that mediate cell proliferation and release antimicrobial molecules and cytokines to activate an immune response. Filariasis is one of the most complex infections of hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Downregulation and impaired activation of NF-κB-p65 and NF-κB-p50/105 in mouse macrophages during the course of infection contributes to macrophage polarization towards M 2 and M reg phenotypes and downregulation of proinflammatory IL-12 release and increased secretion of Th 2 /Th reg cytokines: IL-4 and IL-10, respectively [ 126 ]. IL-10 and IL-12 release is also impaired in human DCs exposed to B. malayi microfilariae [ 130 ]; however, pathologies during infection are associated with increased Th 1 /Th 17 responses [ 131 ] and enhanced angiogenesis [ 132 ]. NF-κB is involved in both angiogenesis [ 133 ] and inflammation [ 134 ] regulation.…”
Section: Helminthsmentioning
confidence: 99%
“…Downregulation and impaired activation of NF-κB-p65 and NF-κB-p50/105 in mouse macrophages during the course of infection contributes to macrophage polarization towards M 2 and M reg phenotypes and downregulation of proinflammatory IL-12 release and increased secretion of Th 2 /Th reg cytokines: IL-4 and IL-10, respectively [ 126 ]. IL-10 and IL-12 release is also impaired in human DCs exposed to B. malayi microfilariae [ 130 ]; however, pathologies during infection are associated with increased Th 1 /Th 17 responses [ 131 ] and enhanced angiogenesis [ 132 ]. NF-κB is involved in both angiogenesis [ 133 ] and inflammation [ 134 ] regulation.…”
Section: Helminthsmentioning
confidence: 99%
“…9 The pathology is known to progress due to elevated inflammatory processes that unfolds in the presence of filarial antigen. [10][11][12] Data from field trials have shown potency of some antibiotics (doxycycline and minocycline) against LF. 7,[13][14][15][16] This notwithstanding, these antibiotics have a longer regimen duration and do not support national treatment programs.…”
Section: Introductionmentioning
confidence: 99%
“…DEC has also been reported to cause severe side effects such as fever, gastrointestinal disturbance, headache, malaise, and skin rash that reduce patient's compliance 9 . The pathology is known to progress due to elevated inflammatory processes that unfolds in the presence of filarial antigen 10–12 …”
Section: Introductionmentioning
confidence: 99%
“…As a dominant NF-κB/IκBα signaling pathways are essential for resistance to heat stress-induced ROS production in pulmonary microvascular endothelial cells regulatory kinase in the classic NF-κB signaling pathway, IκBα serves a prominent role in apoptosis (17). In addition, the IκBα/NF-κB signaling pathway is one of the most popular antitumor targets (18). The results of the present study revealed a novel mechanism for HS-induced NF-κB activation in rat pulmonary microvascular endothelial cells (PMVECs) without IκBα degradation, which differs from the classic NF-κB signaling pathway.…”
Section: Introductionmentioning
confidence: 99%